Social Networks in the Cosponsorship Legislative Behavior: Theoretical Explorations - Ghinea, Gabriela-Nouella (Calitatea Vieții, 2022)
Legislation adoption is a complex process which brings together assorted actors, each with its own array of attributes, strategies and motives. Legislators rely on the web created for a diverse array of functions, from information diffusion to coalition building. Given its heterogeneous nature, legislative cosponsorship networks have gradually become a focus point in the study of collaborative activity in political settings. The article looks into the history of how social network analysis has been adopted in the study of cosponsorship patterns, at the most used methodologies, explanatory variables and applications within this subfield. It looks at the multiple studies that are dealing with the variables facilitating voluntary cooperation, how they may vary in performance given different national contexts, and how personal interests and institutional constraints (or incentives) intertwine. The last chapter deals with research developed using lessons learned from studying legislative networks.